2019
DOI: 10.1186/s12880-019-0383-8
|View full text |Cite
|
Sign up to set email alerts
|

Half-body MRI volumetry of abdominal adipose tissue in patients with obesity

Abstract: BackgroundThe purpose of this study was to determine to what extent the whole volumes of abdominal subcutaneous (ASAT) and visceral adipose tissue (VAT) of patients with obesity can be predicted by using data of one body half only. Such a workaround has already been reported for dual-energy x-ray absorption (DEXA) scans and becomes feasible whenever the field of view of an imaging technique is not large enough.MethodsFull-body abdominal MRI data of 26 patients from an obesity treatment center (13 females and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
(21 reference statements)
0
2
0
3
Order By: Relevance
“…VAT has been linked to metabolic syndrome and cardiovascular mortality (7) and, conversely, VAT loss improves the inflammatory profile (22). A mean ratio of approximately 3.2/1 has been reported for SAT/VAT based on abdominal MRI images in chronically obese adult patients (23). Conversely, in our cat population, the amount of SAT and VAT was very similar at all the examined time points, with a median VAT/SAT ratio of about 0.8 at any analyzed time point.…”
Section: Discussionmentioning
confidence: 99%
“…VAT has been linked to metabolic syndrome and cardiovascular mortality (7) and, conversely, VAT loss improves the inflammatory profile (22). A mean ratio of approximately 3.2/1 has been reported for SAT/VAT based on abdominal MRI images in chronically obese adult patients (23). Conversely, in our cat population, the amount of SAT and VAT was very similar at all the examined time points, with a median VAT/SAT ratio of about 0.8 at any analyzed time point.…”
Section: Discussionmentioning
confidence: 99%
“…Наиболее точно отражают количество абдоминальной жировой ткани срезы, проведенные на уровне 5-10 см выше L4-L5, либо на уровне T12-L1 [33,34]. Поскольку ВЖТ обнаруживается преимущественно в нижней трети живота, где кишечник и органы малого таза не имеют сильной асимметрии, получить достоверные данные о количестве висцерального жира можно без вовлечения в исследование верхних отделов брюшной полости, которые составляют лишь небольшую часть этого жира [35].…”
Section: мртunclassified
“… 5 At present, there are many methods for nutrition assessment in academia, including subjective global assessment, 6 , 7 nutritional risk screening 2002, 8 mini-nutritional assessment, 9 short-form mini-nutritional assessment, 10 , 11 bioelectrical impedance analysis, 12 dual energy X-ray absorptiometry, 13 , 14 computed tomography, 15 and MRI. 16 , 17 Although these methods are more accurate and quantitative, they cannot evaluate the overall obesity of the human body accurately. 18 Studies 19 , 20 have shown that the Heath-Carter anthropometric somatotype can comprehensively consider various factors affecting the human body (such as height, weight, skeletal muscle, body fat, etc.)…”
Section: Introductionmentioning
confidence: 99%